The influence of sleep hygiene education on sleep in professional rugby league athletes - Caia, J.; Scott, T. J.; Halson, S. L.; Kelly, V. G. (Sleep Health, 2018)
Objective: To examine the usefulness of sleep hygiene education on the sleep of professional rugby league athletes during a 10-week period of the competitive season. Design: Case study. Participants: Twenty-four professional rugby league athletes. Measurements: Initially, participants were monitored for a 2-week period using wrist activity monitors allowing baseline estimation of sleep. Following this, 12 athletes attended two 30-minute sleep hygiene education seminars delivered over successive weeks, whereas the remaining 12 athletes received no education. Sleep was monitored in all athletes across the 2-week education period and for a 2-week period 1 month following the end of education. Split-plot analysis of variance and paired t tests were used to examine differences in sleep across the duration of the investigation. Results: An initial sleep hygiene education seminar resulted in an earlier bedtime (effect size [ES] = 0.53 ± 0.48), more time in bed (ES = 0.53 ± 0.49), and increased sleep duration (ES = 0.47 ± 0.44). A second sleep hygiene education seminar resulted in more time in bed (ES = 0.84 ± 0.50) but a reduction in sleep efficiency (ES = 1.15 ± 0.48). One month following sleep hygiene education, sleep behavior was comparable to that observed at baseline. Conclusion: This study shows that sleep hygiene education can lead to positive changes in sleep behavior. However, changes in sleep from education may not be sustained following the initial intervention.